2019
DOI: 10.1002/jcp.28420
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of antidiabetic drugs on adipocytes and adipokine expression

Abstract: Several classes of antidiabetic agents have been developed that achieve their hypoglycemic outcomes via various molecular mechanisms. Adipose tissue is a major metabolic and energy‐storing tissue and plays an important role in many metabolic pathways, including insulin signaling and insulin sensitivity. Adipose tissue monitors and regulates whole body homeostasis via production and release of potent proteins, such as adipokine and adiponectin, into the circulation. Therefore, any agent that can modulate adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 133 publications
0
18
0
Order By: Relevance
“…In this study, we could not confirm that the increased adiponectin concentrations within the first 24 h of a stroke represent a “response” of the human organism. Furthermore, adiponectin levels can be influenced by antidiabetic drugs [50, 51]. However, in this study, serum levels of adiponectin were not influenced by antidiabetic drugs.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we could not confirm that the increased adiponectin concentrations within the first 24 h of a stroke represent a “response” of the human organism. Furthermore, adiponectin levels can be influenced by antidiabetic drugs [50, 51]. However, in this study, serum levels of adiponectin were not influenced by antidiabetic drugs.…”
Section: Discussionmentioning
confidence: 54%
“…It has demonstrated that adipokine modulators are beneficial in the management of diabetic nephropathy (Yaribeygi et al , 2019c). For example, omentin-1, an adipokine modulator, has shown to have great potential in the amelioration of diabetic nephropathy (Song et al , 2018).…”
Section: Mir-27amentioning
confidence: 99%
“…When glycemia decreases, the opposite is observed [24,26]. Since lipids serve as a substrate for glucose production, DM, obesity and other metabolic conditions are straightly correlated, thus explaining why metabolic syndrome is inevitably increasing among humans [27][28][29][30].…”
Section: Pathophysiology Of T2dmmentioning
confidence: 99%